2016
DOI: 10.1021/acschembio.6b00437
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Molecular Rotor for Defining Nucleoside Environment within a DNA Aptamer–Protein Complex

Abstract: The simple 5-furyl-2'-deoxyuridine ((Fur)dU) nucleobase exhibits dual probing characteristics displaying emissive sensitivity to changes in microenvironment polarity and to changes in solvent rigidity due to its molecular rotor character. Here, we demonstrate its ability to define the microenvironment of the various thymidine (T) loop residues within the thrombin binding aptamer (TBA) upon antiparallel G-quadruplex (GQ) folding and thrombin binding. The emissive sensitivity of the (Fur)dU probe to microenviron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 40 publications
6
55
0
Order By: Relevance
“…The TBA DNA's six loop thymidines were replaced by a fluorescent furyl derivative, the 5-furyl-2′-deoxyuridine ( Figure 8 , 10 ), to demonstrate the analog's ability to determine the positional impact of each thymine on the stability and thrombin-binding activity of the TBA GQ [ 131 ]. Earlier NMR studies suggested that T4 and T13 stack strongly with the neighboring G-tetrad and T9 of GGT T GGTG T GGT T GG interacts with G8 of the TGT loop and with the G-tetrad.…”
Section: Stabilization or Destabilization Of A Gq By The Same Syntmentioning
confidence: 99%
“…The TBA DNA's six loop thymidines were replaced by a fluorescent furyl derivative, the 5-furyl-2′-deoxyuridine ( Figure 8 , 10 ), to demonstrate the analog's ability to determine the positional impact of each thymine on the stability and thrombin-binding activity of the TBA GQ [ 131 ]. Earlier NMR studies suggested that T4 and T13 stack strongly with the neighboring G-tetrad and T9 of GGT T GGTG T GGT T GG interacts with G8 of the TGT loop and with the G-tetrad.…”
Section: Stabilization or Destabilization Of A Gq By The Same Syntmentioning
confidence: 99%
“…116 Recent highlights include Tor’s isomorphic RNA alphabet, 17,18 Wilhelmsson’s internucleobase FRET pair, 12,19 Sasaki’s fluorescent sensors for nucleobase damage, 20 and a number of examples of nucleobase surrogates that can report on events in the major groove, such as protein binding. 21,22 Still, significant unmet needs persist. For example, most fluorescent nucleobase analogues are quenched when base stacked, emit only at wavelengths <525 nm, and many perturb duplex structure.…”
mentioning
confidence: 99%
“…The differential binding affinity exhibited by PDS is likely to be due to differences in the physicochemical environment of the G‐tetrad near the diagonal, lateral, and propeller loops 50. In the absence of a change in emission maximum, fluorescence quenching upon ligand binding could be due to derigidification of the fluorophore or a proximal effect, wherein the close vicinity of a polyaromatic ligand with the fluorophore could induce nonradiative dissipation of energy 50, 52…”
Section: Resultsmentioning
confidence: 99%
“…[50] In the ab- sence of ac hange in emission maximum, fluorescencequenching upon ligand bindingc ould be due to derigidification of the fluorophore or ap roximale ffect, wherein the close vicinity of ap olyaromatic ligand with the fluorophore could induce nonradiative dissipation of energy. [50,52] The applicabilityo fn ucleoside probes 1 and 2 in estimating the binding of ligand to H-Telo DNA and TERRA GQs in confined environments was studied by preparing stock solutions of DNA and RNA ONs 5-8 containing increasing concentrations of PDS. The individual stock solution was then added to AOT RMs, such that w 0 was maintained at 20.…”
Section: Probing Ligand Binding In Aqueous Buffer and Rmsmentioning
confidence: 99%